Analisis Kinerja Keuangan PT. Goto Gojek Tokopedia TBK Sebelum Dan Pasca IPO : Laporan Keuangan Tahun 2021-2023 - Neneng Genny S; Minto Yuwono (CV Edujavare Publishing, 2025)
This study analyzes the financial performance of PTS. Goto Gojek Tokopedia TBK focusing on the period before and after the initial public offering (IPO) from 2021 to 2023. The company was officially listed on the Indonesia Stock Exchange through a partnership with Tokopedia in April 2022, with funds allocated for trading on the exchange. This study uses financial ratio analysis such as liquidity, profitability, and solvency costs to assess the impact of the IPO on Goto's financial situation. The results show that although GoTo maintained a healthy liquidity position post-IPO, as reflected by the stable current ratio and quick ratio, its profitability performance showed a downward trend, with increasing losses in net profit margin, Return on Assets (ROA), and Return on Equity (ROE). The increase in the debt ratio after the initial public offering (IPO) indicates that GoTo is increasingly dependent on external financing to support its expansion, which could potentially increase the financial risks faced by the company. Despite successfully raising large funds, the company's profitability has not shown a positive impact in the short term, with hopes of improvement in the future. This study highlights the challenges that companies address following an IPO compared to operational cost management, efficiency and capital utilization for sustainable growth.